2011
DOI: 10.1177/1089253211416255
|View full text |Cite
|
Sign up to set email alerts
|

Early Degeneration of a Bioprosthetic Mitral Valve Complicated by a Large Left Atrial Thrombus

Abstract: The authors report the case of a patient with symptomatic early bioprosthetic mitral valve deterioration in the setting of calcium supplementation. This was further complicated by a large left atrial thrombus despite supratherapeutic anticoagulation and a previously oversewn left atrial appendage. As mechanical valves are less predisposed to calcification in comparison with bioprosthetic implants, the patient underwent a mechanical mitral valve replacement in addition to a left atrial thrombectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
(10 reference statements)
0
1
0
Order By: Relevance
“…Connors et al [27] reported a 71-year-old male who was admitted with dyspnea due to BPVT and calcification of mitral valve prosthesis despite an international normalized ratio (INR) of 4; he recovered following redo MVR. His past medical history included parathyroidectomy, for which he was on daily calcium and vitamin D supplementation.…”
Section: Pathophysiologymentioning
confidence: 99%
“…Connors et al [27] reported a 71-year-old male who was admitted with dyspnea due to BPVT and calcification of mitral valve prosthesis despite an international normalized ratio (INR) of 4; he recovered following redo MVR. His past medical history included parathyroidectomy, for which he was on daily calcium and vitamin D supplementation.…”
Section: Pathophysiologymentioning
confidence: 99%